Manifestaciones cutáneas de enfermedades gastrointestinales - Tapia T., Gabriela; Martínez L., Cristina; Vera G., Valentina; Calderón H., Perla; Poniachik T., Jaime (Revista Hospital Clínico Universidad de Chile, 2018)
The gastrointestinal system is closely related to the skin. Multiple disorders of the gastrointestinal tract that manifest clinically on the skin surface are recognized, which can even occur before establishing the definitive diagnosis of the disease. For this reason, it is necessary that the dermatologist is internalized regarding the wide variety of clinical signs that can guide the etiological study, which requires in most cases, a multidisciplinary management.